2011
DOI: 10.2478/v10011-011-0023-5
|View full text |Cite
|
Sign up to set email alerts
|

Glycans as Biomarkers: Status and Perspectives

Abstract: lanaca koji su kovalentno vezani za poli pep tidnu ki~mu. Dobro je poznat zna~aj prome na u glikozilaciji proteina za nastanak, razvoj i krajnji ishod razli~itih bolesti kod ljudi. Glikani se smatraju jedinstvenim strukturama za di jag nozu, i pra}enje toka bolesti. U »omics« eri, glikom, glika n ski analog proteoma i genoma, predstavlja mogu}i izvor no vih biomarkera. Kreiranje strategije za otkri}e biomarkera zahteva nove principe i platforme za analizu relativno malih koli~ina brojnih glikoproteina. O~ekuje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 125 publications
(99 reference statements)
0
23
0
Order By: Relevance
“…These studies have also demonstrated the potential of employing glycomics of human specimens or glycoproteins isolated from human specimens to define potential glycan biomarkers for cancers of different organs, including breast, colon, esophagus, liver, ovary, pancreas, and prostate. Several recent reviews described the use of both MALDI-MS [21][22][23][24] and LC-ESI-MS in glycan biomarker discovery, in general [21][22][23][25][26][27]].…”
Section: Diagnosis Of Cancer Through Ms-based Glycomicsmentioning
confidence: 99%
“…These studies have also demonstrated the potential of employing glycomics of human specimens or glycoproteins isolated from human specimens to define potential glycan biomarkers for cancers of different organs, including breast, colon, esophagus, liver, ovary, pancreas, and prostate. Several recent reviews described the use of both MALDI-MS [21][22][23][24] and LC-ESI-MS in glycan biomarker discovery, in general [21][22][23][25][26][27]].…”
Section: Diagnosis Of Cancer Through Ms-based Glycomicsmentioning
confidence: 99%
“…MS and LC-MS are currently the method of choice for the characterization of glycans. Several recent reviews have described the use of both MALDI-MS [2427] and LC-ESI-MS in glycan biomarker discovery in general [2426, 2830]. This review is concerned with highlighting the use of MS and LC-MS in defining N- and O-glycans structures as “putative” cancer biomarkers of different organs, including breast, colon, esophagus, liver, lung, ovarian, pancreas and prostate.…”
mentioning
confidence: 99%
“…These functions range from controlling protein folding and clearance rates to mediating events like inflammation, metastasis, and infection to serving as biomarkers of diseases. 4 In fact, an established hallmark of tumorigenesis is the biosynthesis of aberrant glycan chains due to profound changes in metabolism, microenvironment and, as a result, in the expression of glycoprocessing enzymes. 5 These aberrations become more marked as the tumor acquires a more aggressive phenotype.…”
Section: Cancer Glycan Biomarkers -A Historical Perspectivementioning
confidence: 99%